Identifier of regional food presence (IRFP) : a new perspective to evaluate sustainable menus - Ginani, Verônica Cortez (2020)
The menu offered in restaurants must meet different aspects of quality. Cultural elements are related to their acceptance and can contribute to the preservation of habits, sustainable agricultural systems, and the maintenance of biodiversity and sustainability, among other factors. In this context, this research proposes an instrument for classifying menus regarding the presence/absence of regional foods called the identifier of regional foods presence (IRFP) as a new perspective to evaluate sustainable menus. For this, lists of regional preparations and ingredients were prepared for each Brazilian region. Sequentially, we submitted the dishes/ingredients to a developed decision tree for the classification of foods into regional or national foods. The score, based on the presence/absence of regional foods, considered the components of a menu, with zero attributed to a lack of regional ingredients/dishes. For national dishes/ingredients, researchers attributed a minimum score equal to ten. One regional food gave a score of50 to the menu, and with more than one regional food, a daily menu scored 100. The final menu evaluation was based on the mean scores of the menus in each restaurant. Scores between 0–49.9 were considered inadequate; 50–74.9, adequate; and excellent between 75–100. The IRFP was applied to 111 menus with data collected from all the offered dishes. In total, the study evaluated data from 774 recipes from the menus of 37 restaurants located in the five Brazilian regions with a similar operating system. ANOVA was used to verify if there was a statistical difference between the mean score of each Brazilian region (p < 0.05). The average score obtained by the IRFP in menus from Brazilian community restaurants was 80.3 ± 30.9 (excellent), showing a significant difference between the Northeast and Southeast Regions, with a more significant presence of regional foods in the Northeast (87.7 ± 28.7). The use of the IRFP in menus was shown to be easy in its application, contributing to a stimulation of the use of regional items and, consequently, to the direct and indirect benefits generated for the food system and the local population.